2020
DOI: 10.1128/msphere.00884-20
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Serial Multidrug-Resistant Tuberculosis Strains Causing Treatment Failure and Within-Host Evolution by Whole-Genome Sequencing

Abstract: Few studies have focused on the reasons for the low cure rate of multidrug-resistant tuberculosis in China and within-host evolution during treatment, which is of great significance for improving clinical treatment regimens. Acquired resistance events were common during the ineffective treatment, among which resistance to amikacin and high-level moxifloxacin were the most common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Although allelic variation in some other genes was observed in this configuration, it was transient and was not observed to be fixed in the dominant population. This is consistent with other studies documenting long-term infections, with no changes in the presence of fixed SNPs in populations of M. tuberculosis [37,38].…”
Section: Discussionsupporting
confidence: 93%
“…Although allelic variation in some other genes was observed in this configuration, it was transient and was not observed to be fixed in the dominant population. This is consistent with other studies documenting long-term infections, with no changes in the presence of fixed SNPs in populations of M. tuberculosis [37,38].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, these regions should not be considered in SNP calling. and recurrence was classified as being due to relapse if there was a difference of ≤6 SNPs ( Cock et al, 2010 ; Jiang et al, 2011 ; Chen et al, 2020 ; Shanmugam et al, 2021 ). A minimum spanning tree was constructed based on pairwise whole-genome SNP differences using BioNumerics (Version5.…”
Section: Methodsmentioning
confidence: 99%
“… 27–29 Several studies have also shown these gyrA variants to emerge during treatment and to be associated with treatment failure. 7 , 9 , 30 , 31 In this study, we report on clonal interference between the D94G and D94N variants in patient 5 at month 4 with frequencies of 62.16% and 32.35%, respectively, until month 7 when only the D94G variant was present at 100% frequency and dominated the population ( Figure 2 ). While treatment failure was already reported clinically and microbiologically at month 6 for patient 3, we did not detect resistance acquisition genotypically and phenotypically until month 8.…”
Section: Discussionmentioning
confidence: 70%